2018
DOI: 10.1186/s40643-018-0225-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of brewery wastewater using hydroponics planted with vetiver grass in Addis Ababa, Ethiopia

Abstract: Background: Bioremediation is the use of biological interventions for mitigation of the noxious effects caused by pollutants in the environment including wastewater. It is very useful approach for a variety of applications in the area of environmental protection. It has become an attractive alternative to the conventional cleanup technologies that employ plants and their associated microorganisms to remove, contain, or render harmless environmental contaminants.Methods: Three parallel hydroponic treatment syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Similar outcome has been reported earlier 5,13 which were 61 and 63.11% respectively. In a hydroponic experiments, investigated 24,25 showed that vetiver grass has the ability to survive in leachate with COD of 750 mg/L to 2600 mg/L and this research showed that vetiver grass could still survive in the 100% leachate strength in which the COD value was 6930, which is a high COD value. Thus grasses are proved to be an excellent pollution resistant, bio resource and could be used to alleviate the problem of soil contamination.…”
Section: Dry Weight Of Shoots and Roots After Treatmentsmentioning
confidence: 83%
“…Similar outcome has been reported earlier 5,13 which were 61 and 63.11% respectively. In a hydroponic experiments, investigated 24,25 showed that vetiver grass has the ability to survive in leachate with COD of 750 mg/L to 2600 mg/L and this research showed that vetiver grass could still survive in the 100% leachate strength in which the COD value was 6930, which is a high COD value. Thus grasses are proved to be an excellent pollution resistant, bio resource and could be used to alleviate the problem of soil contamination.…”
Section: Dry Weight Of Shoots and Roots After Treatmentsmentioning
confidence: 83%
“…The overall performance of vetiver grass in a PFR-based constructed wetland system was better than in our previous batch study. Specifically, our previous hydroponic batch experiments showed vetiver grass removed only 71% of CIP and 90% of TTC after 7 days [ 56 ]. The flow condition in a PFR system promotes better contact of the antibiotics with vetiver roots, thus facilitating improved removal compared to batch reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Vetiver grass was also reported to withstand extreme conditions like acidic environment (pH = 0.6), concentrated nutrients (nitrate concentrations up to 350,000 mg/L), freezing temperature (5 °F or −15 °C), and drought (up to 15 months) [ 33 , 34 ]. The multipurpose applications of vetiver grass include prevention of soil erosion [ 35 , 36 ], protection of river banks [ 37 , 38 , 39 ], removal of lead from soil [ 40 , 41 , 42 , 43 ], management of acid mine drainage impacted soil and water [ 44 , 45 , 46 ], removal of explosives from soil and water [ 44 , 47 , 48 , 49 , 50 ], decontamination of heavy metals from landfill leachate [ 51 , 52 ], removal of antibiotics from soil and water [ 53 , 54 , 55 ], and removal of nutrients (nitrogen and phosphorus) [ 56 ], etc. Our previous batch studies have shown that vetiver grass is not only capable of removing antibiotics (TTC and CIP) from wastewater but also degrading and metabolizing antibiotic molecules [ 54 , 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Mollard et al (2013) have also reported that Typha latifolia is effective in mitigating nutrient-rich wastewater. Another TN removal effectiveness study of these macrophytes was investigated separately, and the Cyperus alternifolius-based treatment of sewage wastewater was able to remove 59.84% of TN at MLR of 940 mgm −2 day −1 in a vertical constructed wetland treatment system (Bilgin et al 2014), while Typha latifolia-based treatment of raw brewery wastewater able to achieve 28-46% of TN at 5 days HRT and HLR of 10 cmday −1 (Worku et al 2018). Generally, the present result had higher than Jamshidi et al (2014) reported TN removal efficiency of 71.9% at ½ day HRT operation using a bio-rack wetland planted with Phragmites sp., and Typha sp.…”
Section: Pollutant Removal Efficiencymentioning
confidence: 99%
“…Different studies reported that Cyperus alternifolius and Typha latifolia-planted HSSFCW treatment system showed good removal efficiencies of organic matter and nutrients; Cyperus alternifolius-planted HSSFCW showed promising removal performance of 95% COD at 12 days HRT, and 93% TSS at 6 days HRT (Sa'at et al 2017), while Typha latifolia achieved 92% TSS and 79% COD at HRT of 4.7 days (Ciria et al 2005). In the case of nutrient removals, Bilgin et al (2014) reported that the Cyperus alternifolius-based treatment system removed 59.84% of TN, while Typha latifolia achieved 28-46% removal of TN from raw brewery wastewater at 5 days (Worku et al 2018). Similarly, Cyperus alternifolius achieved 73% TP removal efficiency from aerobic palm oil mill effluent at 21 days HRT (Rezaie and Salehzadeh 2014), and Typha latifolia removed 39% of TP at HRT of 4.7 days (Ciria et al 2005).…”
Section: Introductionmentioning
confidence: 99%